Altered Brain Structural Reorganization and Hierarchical Integrated Processing in Obesity - Zhang, Peng; Wu, Guo-wei; Tang, Li-rong; Yu, Feng-xia; Li, Meng-yi; Wang, Zheng; Yang, Zheng-han; Zhang, Zhong-tao; Lv, Han; Liu, Yang; Wang, Zhen-chang (Frontiers in Neuroscience, 2022)
The brain receives sensory information about the food, evaluates its desirability and value and responds with approach or withdrawal. The evaluation process of food in the brain with obesity may involve a variety of neurocircuit abnormalities in the integration of internal and external information processing. There is a lack of consistency of the results extant reported for aberrant changes in brain with obesity that prohibits key brain alterations to be identified. Moreover, most studies focus on the observation of neural plasticity of function or structural, the evidence for functional and structural correlations in the neuronal plasticity process of obesity is still insufficient. The aims of this article are to explore the key neural structural regions and the hierarchical activity pattern of key structural nodes and evaluate the correlation between changes of functional modulation and eating behavior. Forty-two participants with obesity and thirty-three normal-weight volunteers were recruited. Gray matter volume (GMV) and Granger causality analysis (GCA) were performed using the DPARSF, CAT12 and DynamicBC toolbox. Compared to normal-weight group, obesity group exhibited significantly increased GMV in left parahippocampal gyrus (PG). Obesity group showed decreased causal inflow to the left PG from the left orbitofrontal cortex (OFC), right calcarine and bilateral supplementary motor area (SMA). Decreased causal outflow to the left OFC, right precuneus and right SMA from the left PG, as well as increased causal outflow to the left middle occipital gyrus (MOG) were observed in obesity group. Negative correlations were found between DEBQ-External scores and causal outflow from the left PG to the left OFC, DEBQ-Restraint scores and causal inflow from the left OFC to the left PG in obesity group. Positive correlation was found between DEBQ- External scores and causal outflow from the left PG to the left MOG. These results show the increased GMV in the PG may play an important role in obesity, which may be related to devalued reward system, altered behavioral inhibition, and the disengagement of attentional and visual function for external signals. These findings have important implications for understanding neural mechanisms in obesity and developing individual-tailored strategies for obesity prevention.